Prison health services across ten central prisons in Cameroon - Jürgen Noeske; Norbert F. Ndi; Fabrice H.M. Nga; Gérald Mely; Christopher Kuaban (AOSIS, 2023)
In 2021, Cameroon held approximately 26,300 inmates in 84 prisons. The Ministry of Justice manages health services in prisons. Conclusive data concerning health care in prisons are lacking. Herein, we present the results of an assessment of health care provision and delivery in 10 central prisons. We adopted mixed methods, including document review, observations, interviews with the Ministry of Justice and prison facility officials, and inmate focus group discus- sions (FGDs). The 6 building blocks of the World Health Organization's health system framework guided the data collection. Moreover, we collected data on imprisonment conditions. Ministerial authorisation and verbal informed consent were obtained for all activities. There were a total of 17,126 inmates, with the prison populations ranging from 353 inmates to 4,576 inmates. The majority of prisons were char- acterised by huge overcrowding (mean 301%). The 10 central prisons operated infirmaries with insufficient space and equip- ment. Compared with the civilian health sector, the numeric ratio of paramedical personnel/inmates was favourable (1:3.4 vs. 1:0.5 p. 1,000 pop, respectively). Recent admissions were screened for the coronavirus disease 2019, tuberculosis (TB), and human immunodeficiency virus (HIV). Moreover, the inmates were diagnosed for current pathologies and lesions. For the treatment of chronic diseases and medical emergen- cies, the prison health services bridged service gaps on a case-by-case basis through informal arrangements with the civilian health sector. The service quality control was limited to those performed by the TB and HIV/acquired immune deficiency syndrome control programmes. Health data was collected and transmitted with a multitude of data collection tools, without standardisation and systematic verification. The primarily reported problems comprised the scarcity of resources and the absence of an effective oversight of resource management and service quality performance entailing gover- nance problems. Participants in FDGs esteemed the quality of treatment as poor unless paid for in cash, and denounced severe difficulties for access to care outside the prisons when required. For meeting the standard minimum rules for the treatment of inmates, prison health care in Cameroon should fill the crucial gaps involving imprisonment conditions, access to health services, and accountability. Regarding chronic underfunding, intensifying collaboration with the civil health sector may partially address the problem.